Oxide Semiconductor for Advanced Memory Architectures: Atomic Layer Deposition, Key Requirement and Challenges - Lee, Chi‑Hoon; Ryu, Seong‑Hwan; Hwang, Taewon; Kim, Sang‑Hyun; Kim, Yoon‑Seo; Park, Jin‑Seong (Nano-Micro Letters, 2026)
Oxide semiconductors (OSs), introduced by the Hosono group in the early 2000s, have evolved from display backplane materials to promising candidates for advanced memory and logic devices. The exceptionally low leakage current of OSs and compatibility with three-dimensional (3D) architectures have recently sparked renewed interest in their use in semiconductor applications. This review begins by exploring the unique material properties of OSs, which fundamentally originate from their distinct electronic band structure. Subsequently, we focus on atomic layer deposition (ALD), a core technique for growing excellent OS films, covering both basic and advanced processes compatible with 3D scaling. The basic surface reaction mechanisms—adsorption and reaction—and their roles in film growth are introduced. Furthermore, material design strategies, such as cation selection, crystallinity control, anion doping, and heterostructure engineering, are discussed. We also highlight challenges in memory applications, including contact resistance, hydrogen instability, and lack of p-type materials, and discuss the feasibility of ALD-grown OSs as potential solutions. Lastly, we provide an outlook on the role of ALD-grown OSs in memory technologies. This review bridges material fundamentals and device-level requirements, offering a comprehensive perspective on the potential of ALD-driven OSs for next-generation semiconductor memory devices. Highlights: 1 This review outlines the emergence of oxide semiconductors as promising channel materials for high-density, low-power next-generation memory applications. 2 Adsorption and reaction mechanisms of atomic layer deposition have enabled the design of high-performance oxide semiconductors for next-generation memory applications. 3 This review discusses key challenges toward successfully integrating oxide semiconductors into next-generation memory devices.